Sinergi Manajemen Organisasi dan Nilai Tafsir Q.S. Ash-Shaff: 4 dalam Membangun Tim Dakwah yang Solid dan Efektif di Era Digital - Moh. Bahrudin; Anwar Mukti; Agung Mandiro Cahyono; M. Luqman Hakim; Ahmad Nur Fathoni; Muhammad Burhanudin Nur Karim (Sciences du Nord Community Service, 2024)
The digital era presents significant challenges for da'wah organizations, including team disintegration, ineffective communication, and burnout due to unstructured management. Addressing these issues requires a synergy between contemporary organizational management and Qur'anic values, particularly the metaphor of a "solid wall" from Q.S. Ash-Shaff: 4, which emphasizes unity and collective strength. This study aims to develop an integrative training module that combines modern management principles with contextual interpretation of Q.S. Ash-Shaff: 4, enhance team cohesion, communication effectiveness, and resilience, and establish a value-based leadership and collaboration model. Employing an action research approach with experiential learning, the program involved organizational diagnosis, participatory workshops, digital da'wah project simulations, and comprehensive evaluation. Data were collected through team effectiveness questionnaires, observations, focus group discussions, and analysis of digital team performance. The results demonstrate increased team cohesion, clearer role distribution, and more efficient meetings, alongside the creation of a Standard Operating Procedure (SOP) that internalizes shaffan values. Furthermore, communication patterns shifted from rigid hierarchies to adaptive collaboration, reflected in improved digital content quality and responsiveness. The findings affirm that systematic integration of management science and Qur'anic values effectively transforms da'wah teams, strengthening both operational and intrinsic faith-based commitment for impactful digital da'wah.